SKIMMING READING TECHNIQUES ON THE ABILITY TO IDENTIFY INTRINSIC DRAMA TEXT ELEMENTS - Agus Sulaeman; Enawar Enawar; Supyan Sori; Achmad Suherman (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2021)
This study aims to determine the use of reading techniques that are effective and efficient, and to determine whether there is an effect of skimming reading techniques on students' reading comprehension skills to identify the intrinsic elements present in drama texts read by grade VIII students of SMP Muhammadiyah Tangerang City. This research is a quantitative research. Data collection techniques using tests, namely pretest and posttest. The results of this study indicate the influence of the ability to identify the intrinsic elements of drama text on students who use skimming reading techniques. This effect has been carried out with the results of the t-test. Then it shows the results of t count 0.233 <t table 1.977, t count is smaller than t table, this shows that there is no significant difference between the experiment class students and the control class students on the ability to identify the intrinsic elements of drama text. After the pretest is done posttest to find out, it shows the results of t count 1.982> t table 1,800, t count is greater than t table shows that there is a difference in the ability to identify the intrinsic elements of drama text between students who receive learning about the use of skimming reading techniques and students who get conventional learning. From the data obtained like what is listed above, it can be concluded that there is an effect of using skimming reading techniques on the ability to identify the intrinsic elements of drama text in class VIII students of SMP Muhammadiyah Tangerang City